ANALISIS EFEKTIVITAS DAN EFISIENSI PENERIMAAN RETRIBUSI DAERAH PADA DINAS PENDAPATAN, PENGELOLAAN KEUANGAN DAN ASET DAERAH KABUPATEN BENGKULU TENGAH - Dirasmi, Sipti; Soleh, Ahmad (Institut Agama Islam Bengkulu, 2016)
Effectiveness And Efficiency Analysis Revenue Levies At the Department of Revenue, Finance and Asset Central Bengkulu District. To increase the levies is necessary to the effectiveness and efficiency of the reception levies. One of them through the subject and object of local revenue, thereby increasing the productivity of PAD. The purpose of this study to determine the effectiveness and efficiency of reception levies on the Department of Revenue, Asset Finance Central Bengkulu regency. Methods of data collection using documentation. The analytical tool used is the ratio of the effectiveness and efficiency ratios. The results showed that the effectiveness of retribution Central Bengkulu Regency in the year 2012 amounted to 24.69% and the criteria are not effective because many of the target sources of retribution were not realized. In 2013 amounted to 94.56% effective with sufficient criteria whereas in 2014 amounted to 111.18% with a very effective criteria for the Government Central Bengkulu in this case the Department of Revenue, Finance and Asset Management Middle Bengkulu regency has evaluated by preparing a revenue target levy that has the potential to be realized. The efficiency level of retribution Central Bengkulu District from 2012-2014 year is already included in the criteria is very efficient, because the efficiency ratio below 10%.Key Words: Effectiveness, Efficiency, Retribution, Central Bengkulu District